A Responsibility to the World: Saramago, Politics, Philosophy - Baltrusch, Burghard; Salzani, Carlo; Vanhoutte, Kristof K. P.; SpringerLink (Online service) (Berlin : Frank & Timme GmbH : Imprint: Frank & Timme, 2023)
In a 1987 interview, José Saramago eloquently expressed what could be considered his political-philosophical manifesto: Human beings should not content themselves with the role of mere observers. They bear a responsibility to the world; they must actively engage and intervene. In 1998 the celebrated writer was honoured with the Nobel Prize for Literature. So Saramago did not only as a human being and a citizen, but also as an artist refuse to be a passive observer. Despite his profound and always critical pessimism, he tirelessly propelled both his public and artistic persona toward impactful actions and interventions, showcasing an unwavering dedication to reshaping the world. This volume seeks to delve into this facet of his legacy, exploring it from diverse political and philosophical perspectives. This is an open access book.
Accessibility summary: This PDF eBook is produced by a third-party. We have requested that the file be made accessible and compliant with the European Accessibility Act (EAA). However, we have not been able to fully verify its compliance with recognized accessibility standards (such as PDF/UA or WCAG). For detailed accessibility information, please refer to the original publisher s website. If you require an accessible version of this content, please contact accessibilitysupport@springernature.com. We are committed to improving accessibility and will work with the publisher to meet your needs wherever possible.
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Literature, Modern -- 20th century; Ethnology -- Latin America; Culture; Twentieth-Century Literature; Latin American Culture